A Sequential One-Pot Protocol for the Synthesis of Dihydrobenzo[6,7]indolo-[3′,4′:3,4,5]azepino[2,1-a]isoquinolines Using a Gold–Silver Combined Catalyst - Saifuddin, Mohammad; Samala, Srinivas; Krishna, Deevi G. Venkata; Kundu, Bijoy (Synthesis, 2013)
A sequential one-pot protocol for the synthesis of indole-based peri-annulated polyheterocycles using trifluoroacetic acid and a gold–silver combined catalyst system is described. The reaction is thought to proceed via an imine formation–cationic π-cyclization–alkyne activation–intramolecular hydroamination sequence to yield novel dihydrobenzo[6,7]indolo[3′,4′:3,4,5]azepino[2,1-a]isoquinolines in good yields.
Keywords: polyheterocycles; alkyne; indole; annulation; Lewis acid; regioselective